Correlation between the age of the subducting Cocos plate and the geometry of the Wadati- Benioff zone under Nicaragua and Costa Rica - Protti, Marino (1981)
This work integrates six tectonic feautures related to the subduction of the Cocos plate under the Caribbean plate along the souhern terninus of the Middle America Trench (Nicaragua and Costa Rica) into a self-consistent model. These tectonic features are: 1) The shallowing of Middle America Trench morphology from NW to SE; 2) The decrease of maximum depth of intraplate Wadati-Benioff zone earthquakes from NW to SE; 3) The shallowing of the Wadati- Benioff zone dip angle in the same direction; 4) The existence of a sharp contortion in the subducted Cocos plate; 5) The abrupt disappearance of intraplate earthquakes deeper than 50 km in central Costa Rica, east of 830 55 W; and 6) The termination of the Central America Volcanic Chain in central Costa Rica. The subduction of the Cocos Ridge under southern Costa Rica has traditionally been used as the mechanism to explain most of the above mentioned features. The Cocos Rigde started subducting only about one million years ago and therefore its subducted portion is no longer than 90 km. Even if the subduction of this ridge had started earlier, the presence of the Panama Fracture Zone limits its NE extension to less than 100 km from the trench, and therefore it can not be responsible for regional changes in the Wadari-Benioff zone several hundred kilometers away. A new model that considere along- trench varations in age of the subducted Cocos plate may primarily explain the geometry of the Wadati-Benioff zone under Nicaragua and Costa Rica, and regional tectonic changes in the ovarriding Caribbean plate.